A Method for Dynamically Identifying Equivalent Mathematical Model Parameters of Power Electronic System Based on Digital Filter. Issue 1 (1st January 2022) - Peng, Huiming; Maksim Popov, G; Li, Feng; Lu, Zhiyu
Abstract: In practice, most mathematical calculations and analysis methods to study the transients of power electrical equipment are based on the use of its idealized mathematical description and, as a result, do not adequately reflect the real dynamic characteristics of the combined power systems. One of the reasons, the use of unreliable initial parameters of the mathematical model during numerical experiments. In this article, a method is developed, the synthesis of equivalent models of a given structure is carried out using methods of parametric identification of dynamic systems. Digital filters designed to increase the reliability of the measurement and information part of modern microprocessor systems are described. There is also an assessment of their speed and error in the numerical solution of the problem of restoring useful and primary electrical signals, as well as methodological and practical recommendations for choosing the sampling frequency of analog-digital transformations in time are given.